EFL Students’ Digital Literacy: Barriers to Development and Effective Web Application Programs - Annisa Luthfia Dayu Rahmah; Eryansyah Eryansyah; Sary Silvhiany (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2021)
This study was a mixed method research which was aimed to examine EFL students' digital literacy skills, as well as the factors impacting their growth and effective web application programs for enhancing their digital literacy skills. This study was conducted at a state-owned university in South Sumatra Province where the participants involved were the sixth semester students of English Education Study Program students from the university. Questionnaires (adapted from Ravitz, 2014) and interviews were used to gather data for the study. The questionnaire data were collected and analyzed using Google form while the interview data were collected through Zoom meetings and were analyzed using thematic analysis. Based on the findings of this study, the vast majority of sixth semester English Education Study Program students were in good to excellent level of digital literacy. More than half of them believed that the lack of digital devices on campus was the most significant problem impeding their development of digital literacy abilities. Furthermore, the vast majority of the participants (90,3%) thought YouTube was the most influential web application program for improving their digital literacy skills.